2006
DOI: 10.1093/carcin/bgi326
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA mutations in oral squamous cell carcinoma

Abstract: It has previously been demonstrated that mitochondrial DNA (mtDNA) mutations within the ND2 gene of histologically normal parotid salivary gland tissue of smokers may be molecular biomarkers for smoking-induced mtDNA damage. Oral squamous cell carcinoma (SCC) is strongly related to cigarette smoking; therefore, we used PCR and direct sequencing to establish whether mtDNA mutations were also present in oral SCC which could be used as additional biomarkers for smoking-associated DNA damage. In addition to search… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
64
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(73 citation statements)
references
References 36 publications
9
64
0
Order By: Relevance
“…9 Head and neck squamous cell carcinomas arise through premalignant intermediates and may be merely morphologic manifestations of accumulated genetic alterations. 20 In keeping with this molecular tumour progression model, studies have shown that mtDNA increases according to histopathologygrade, a phenomenon that may be a feedback mechanism that compensates for a generalised decline in respiratory chain function. Therefore, high mtDNA content may be another marker of genetic alteration, a measure of relative DNA injury, and a surrogate measure of histopathology grade.…”
Section: Role Of Tumour Suppressor Gene Sdh Mutation In Tumour Formationmentioning
confidence: 90%
See 3 more Smart Citations
“…9 Head and neck squamous cell carcinomas arise through premalignant intermediates and may be merely morphologic manifestations of accumulated genetic alterations. 20 In keeping with this molecular tumour progression model, studies have shown that mtDNA increases according to histopathologygrade, a phenomenon that may be a feedback mechanism that compensates for a generalised decline in respiratory chain function. Therefore, high mtDNA content may be another marker of genetic alteration, a measure of relative DNA injury, and a surrogate measure of histopathology grade.…”
Section: Role Of Tumour Suppressor Gene Sdh Mutation In Tumour Formationmentioning
confidence: 90%
“…They found that both tumours and saliva from head and neck cancer patients contained an increased amount of mitochondrial DNA content. [19][20][21][22] It has been shown that mitochondrial mutations result in an increase in mitochondrial mass which could be due to nuclear encoded factors that are translocated into mitochondria resulting in proliferation. 19,21 It was found that the in vitro effect of tobacco smoke extract and tobacco smoke exposure and its effect on mitochondrial function and mitochondrial contents in both acute and chronic setting.…”
Section: Role Of Tumour Suppressor Gene Sdh Mutation In Tumour Formationmentioning
confidence: 99%
See 2 more Smart Citations
“…The timing of other mitochondrial mutations in the progression from normal mucosa to invasive tumor has not been well established (18,19). The D-loop, which has propensity for mutation, was found to carry mutations in 21% to 53% of HNSCC (20,21). Sequencing of 80% of the mitochondrial genome using conventional methods has revealed mutation in 46% in a limited cohort of HNSCC (2).…”
mentioning
confidence: 99%